Different sample preparation and detection methods for normal and lung cancer urinary proteome analysis. - Supachok Sinchaikul (2018)
The urinary proteome is known to be a valuable field of study related to human physiological functions because many components in urine provide an alternative to blood plasma as a potential source of disease biomarkers useful in clinical diagnosis and therapeutic application. Due to the variability and complexity of urine, sample preparation is very important for decreasing the dynamic range of components and isolating specific urinary proteins prior to analysis. We discuss many useful sample preparation methods in this chapter, including those of lung cancer urine samples. In addition, protein detection methods are also crucial in visualizing protein profiles and for quantification of protein content in urine samples from both normal donor and lung cancer patients. This chapter also provides alternative choices of urine sample preparation and detection methods for selective use in urinary proteome analysis and for identifying urinary protein markers in lung cancer and other diseases.